Cosmogenic neutron production at the Sudbury Neutrino Observatory - Aharmim, Bassam; Ahmed, S. N.; Anthony, A. E.; Barros, N.; Beier, E. W.; Bellerive, A.; Beltran, B.; Bergevin, M.; Biller, S. D.; Bonventre, R.; Boudjemline, K.; Boulay, M. G.; et al. (Physical review, 2019)
Neutrons produced in nuclear interactions initiated by cosmic-ray muons present an irreducible background to many rare-event searches, even in detectors located deep underground. Models for the production of these neutrons have been tested against previous experimental data, but the extrapolation to deeper sites is not well understood. Here we report results from an analysis of cosmogenically produced neutrons at the Sudbury Neutrino Observatory. A specific set of observables are presented, which can be used to benchmark the validity of geant4 physics models. In addition, the cosmogenic neutron yield, in units of 10−4 cm2/(g⋅μ), is measured to be 7.28±0.09(stat)+1.59−1.12(syst) in pure heavy water and 7.30±0.07(stat)+1.40−1.02(syst) in NaCl-loaded heavy water. These results provide unique insights into this potential background source for experiments at SNOLAB.
Gesehen am 14.08.2020